Magnesium as a potential complementary treatment for ADHD - a review of recent literature - Smykiewicz, Karolina; Michalczewska, Aneta; Wierzejska, Natalia; Pach, Magdalena; Nowak, Agnieszka; Fugas, Agnieszka; Chmielowiec, Zuzanna; Partyka, Alicja; Dziedzic, Mariola; Dobrzańska, Justyna (Journal of Education, Health and Sport, 2024)
Attention-deficit/hyperactivity disorder (ADHD) is a relatively common neurodevelopmental mental disorder affecting an estimated 7.2% of children and adolescents, and 2.5% of adults. It manifests primarily through inattention, impulsivity, and hyperactivity. Multimodal treatment approaches are recommended, addressing the psychological, behavioral, vocational, and educational needs of patients and their families. Conventional therapies include pharmacologic interventions (e.g., psychostimulants) and non-pharmacologic strategies (e.g., psychotherapy, cognitive-behavioral therapy). The ongoing search for novel treatment options focuses on improving cognitive function, psychological well-being, and ADHD symptomatology. Nutritional interventions with vitamins and minerals are emerging as potential complementary or adjunctive therapies. This review summarizes recent literature (past 5 years) on the relationship between magnesium and ADHD, encompassing observational studies, interventional trials, and meta-analyses. Evidence from recent publications suggests that children with ADHD have reduced magnesium levels and that magnesium supplementation improves symptoms. However, these studies do not definitively establish the exact cause-and-effect relationship between magnesium and ADHD. Current data are insufficient to recommend magnesium for routine ADHD treatment. High-quality, large-scale, and long-term studies are necessary to definitively understand the magnesium-ADHD link and to evaluate the effectiveness and safety of magnesium supplementation as an adjunct therapy. These studies should define optimal doses, forms, and duration of supplementation for safe and effective clinical use.